On-ice sweat rate, voluntary fluid intake, and sodium balance during practice in male junior ice hockey players drinking water or a carbohydrate-electrolyte solution - Palmer, M. S.; Logan, H. M.; Spriet, L. L. (Applied Physiology, Nutrition, and Metabolism, 2010)
Abstract: This study evaluated the repeatability of hydration and sweat measurements taken during on-ice hockey practices with players drinking only water, and determined whether having only a carbohydrate-electrolyte solution (CES) to drink during practices decreased fluid intake or affected other hydration and (or) sweat measures. All testing was conducted on elite players of an Ontario Hockey League team (±SE; mean age, 17.6 ± 0.3 years; mean height, 182.9 ± 1.4 cm; mean body mass, 83.0 ± 1.7 kg). Players were studied 3 times over the course of 6 weekly on-ice practices (±SE; mean playing time, 1.58 ± 0.07 h; mean temperature, 11.4 ± 0.8 °C; mean relative humidity, 52% ± 3%). There was strong repeatability of the measured hydration and sweat parameters between 2 similar on-ice practices when players drank only water. Limiting the players to drinking only a CES (as opposed to water) did not decrease fluid intake during practice (±SE; mean CES intake, 0.72 ± 0.07 L/h vs. mean water intake, 0.82 ± 0.08 L/h) or affect sweat rate (1.5 ± 0.1 L/h vs. 1.5 ± 0.1 L/h), sweat sodium concentration (72.4 ± 5.6 mmol/L vs. 73.0 ± 4.4 mmol/L), or percent body mass loss (1.1% ± 0.2% vs. 0.9% ± 0.2%). Drinking a CES also improved sodium balance (-2.1± 0.2 g/h vs. -2.6 ± 0.3 g/h) and provided the players with a significant carbohydrate (43 ± 4 g/h vs. 0 ± 0 g/h) during practice. In summary, a single field sweat test during similar on-ice hockey practices in male junior hockey players is sufficient to evaluate fluid and electrolyte balance. Also, a CES does not affect voluntary fluid intake during practice, compared with water, in these players. The CES provided some salt to offset the salt lost in sweat, and carbohydrate, which may help maintain physical and mental performance in the later stages of practice.